2022
DOI: 10.1002/acr.24461
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Childhood‐Onset Systemic Lupus Erythematosus Diagnosis Relative to Menarche and the Impact on Final Adult Height

Abstract: Objective The aim of this study was to examine the impact of timing of a childhood‐onset systemic lupus erythematosus (SLE) diagnosis relative to menarchal status, on final height, accounting for disease‐associated factors. Methods We conducted a cohort study of female patients age <18 years at childhood‐onset SLE diagnosis, followed at a tertiary care pediatric center from July 1982 to March 2016 and restricted to patients with documented age of menarche and final height. We compared final height between pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…It was also recorded that SLE girls who had a younger age at diagnosis and a longer duration of therapy were found to have a signi cant delay in breast development as well as a delay in attainment of menarche. This is in tandem with observations made among Canadian SLE patients (15) who had a younger age at onset and also had a signi cant delay in breast development and age at menarche (p < 0.05). These cumulative ndings suggest a strong correlation that disease activity directly affects the pubertal status in SLE patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It was also recorded that SLE girls who had a younger age at diagnosis and a longer duration of therapy were found to have a signi cant delay in breast development as well as a delay in attainment of menarche. This is in tandem with observations made among Canadian SLE patients (15) who had a younger age at onset and also had a signi cant delay in breast development and age at menarche (p < 0.05). These cumulative ndings suggest a strong correlation that disease activity directly affects the pubertal status in SLE patients.…”
Section: Discussionsupporting
confidence: 86%
“…Despite being a major manifestation, growth and pubertal development in systemic lupus erythematosus, are not well studied 13 and still remains an under-researched area. There are only a few reports from the west suggesting compromised physical growth (12)(13)(14)(15)(16)(17) as well as delayed pubertal attainments (11,15,16,18) among children and adolescents with SLE. There hasn't even been a single study so far that documents the auxological pattern in Indian SLE children.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who developed SLE during childhood are shorter than those who developed Frontiers in Genetics frontiersin.org it during adulthood (Heshin-Bekenstein et al, 2018). Female patients who developed SLE before menarche are shorter than those who developed SLE after menarche (Sontichai et al, 2022). Research focusing on children with SLE has also identified sex and hormone use as factors that lead to reduced final height in patients with SLE (Jongvilaikasem and Rianthavorn, 2021;Ponin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Premature menarche has been considered a risk factor for the development of SLE, 5 while the development of SLE prior to menarche may delay menarche in patients. 6,7 In contrast, a later AAM has been observed to reduce the risk of SLE in black women, and SLE patients may experience a later menarche than healthy controls. 8 Furthermore, pregnancy in patients with SLE is usually associated with greater risk, as pregnancy itself often causes recurrences of SLE.…”
Section: Introductionmentioning
confidence: 99%